PERAN PINJAMAN DANA BERBASIS ONLINE MELALUI APLIKASI TERHADAP PEREKONOMIAN DI INDONESIA - Santi, Mei (EKSYAR: Jurnal Ekonomi Syari'ah & Bisnis Islam, 2019)
One of the facilities offered by Indonesian financial institutions is credit. Where in Indonesia, demand for credit is very high. To support this, online loans have emerged that have an important role as one of the government partners who will contribute to channeling more loans to customers. The role of online loans through applications with various advantages which include: fast processing; easy terms; flexible; credit calculator; as well as a variety of products, are expected to help equal distribution to the public to become users of financial services. With access to finance for all levels of society it will certainly be able to help drive the economy in Indonesia and provide a major contribution to the progress of economic development in Indonesia in particular.